2011
DOI: 10.1007/s00289-011-0676-8
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening polymerization of cyclic esters in the presence of choline/SnOct2 catalytic system

Abstract: Low-molecular weight poly(e-caprolactone), polylactides, and copolymers of e-caprolactone and lactide were synthesized by ring-opening polymerization of cyclic monomers with choline (CHOL) as a initiator and SnOct 2 as a catalyst. Polymerization was conducted in bulk (120-160°C) with high yield. Effects of temperature, reaction time, and CHOL dosage on the polymerization process were examined. Structure of products was characterized by means of MALDI-TOF, IR, and NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Several research groups have used Sn(Oct) 2 as catalyst together with benzyl alcohol as initiator to study ROP of polycaprolactones, and different mechanisms have been suggested . Our proposed mechanism of the grafting reaction can be seen in Fig.…”
Section: Characterization Of Modified Fibers and Compositesmentioning
confidence: 99%
“…Several research groups have used Sn(Oct) 2 as catalyst together with benzyl alcohol as initiator to study ROP of polycaprolactones, and different mechanisms have been suggested . Our proposed mechanism of the grafting reaction can be seen in Fig.…”
Section: Characterization Of Modified Fibers and Compositesmentioning
confidence: 99%
“…The results clearly indicate that typical 1 H NMR chemical shifts at 1.38 (C H 2 CH 2 CH 2 COO), 1.64 (C H 2 CH 2 COO), 2.30 (C H 2 COO), 4.06 (C H 2 OCO), and 3.65 (C H 2 CH) ppm were associated with PCL in both spectra. 13 Incorporation of 1-NM into PCL chains is confirmed with the proton peaks at 5.58 (C 10 H 7 C H 2 OH) and 7.30–8.00 (C 10 H 7 CH 2 ) ppm which can be observed in Figure S1a.…”
Section: Resultsmentioning
confidence: 68%
“…Any change in the chemical environment of the protons through chemical interactions is generally reflected by the disappearance of existing peaks, appearance of new set of peaks or a chemical shift. It is noteworthy that the split signals corresponding to methylene of the terminal groups (CH 2 OH) of neat PLA appearing at δ = 3.719, 3.708 ppm, are not seen in the composite. This indicates the interaction of Org‐Paly with the PLA matrix.…”
Section: Resultsmentioning
confidence: 97%